2014
DOI: 10.1111/hex.12283
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to effective coverage of Intimate Partner Violence services for immigrant women in Spain

Abstract: Objective To explore service providers' perceptions in order to identify barriers and facilitators to effective coverage of Intimate Partner Violence (IPV) services for immigrant women in Spain, according to the different categories proposed in Tanahashi's model of effective coverage.Methods A qualitative study based on 29 in-depth personal interviews and four group interviews with a total of 43 professionals working in public services (social and health-care services, women's refuges, the police force, the ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…It should be noted, however, that providing appropriate support to South Asian women who have experienced IPV may require special considerations. For example, potential language barriers, lack of accessibility of health services, legal services, and social support services, and culture need to be taken into account to ensure that appropriate support is available and accessible [22][23][24]. There is evidence that social services are underutilized by South Asian women and other ethnic minorities in North America [22,23] so efforts must be made to be inclusive of all women.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that providing appropriate support to South Asian women who have experienced IPV may require special considerations. For example, potential language barriers, lack of accessibility of health services, legal services, and social support services, and culture need to be taken into account to ensure that appropriate support is available and accessible [22][23][24]. There is evidence that social services are underutilized by South Asian women and other ethnic minorities in North America [22,23] so efforts must be made to be inclusive of all women.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this concept analysis showed that immigrant and refugee women experienced cultural alienation from health care providers and struggled finding adequate health care and shelter for themselves and their children 17,18,26 . Nurses can support these women by making warm referrals to different groups, 1 but not limited to migrant organizations, Women Infant and Children (WIC) programmes, refugee cultural centers, and churches to increase sociocultural integration and reduce potential consequences of acculturative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In order for someone to experience cultural alienation, there has to be at least one majority and minority group involved. It is derived from two different senses (a) biological characteristics 17–24 like race or sex and (b) values 19,20,23–30 such as tastes or preferences. Its main antecedents were the following: (1) Identification with racial or ethnic minority group; (2) Sexual minority; (3) Disability; (4) Chronic illness; (5) Insufficient and inadequate sense of belonging, community, or refuge; (6) Nontraditional health‐care practices and preferences; and (7) Threat to loss of way of life and culture.…”
Section: Concept Analysis Methodsmentioning
confidence: 99%
“…These factors plus the understanding of their legal options, were important elements in helping women move out of abusive relationships (29) . Schutz's concept of 'social action' links an individual's choice of action to the actions of others: IPV victims might do nothing because they saw no positive support available to them; or they might do something if they felt that others' (police, doctor, social worker) actions would positively influence the outcome of their action.…”
Section: Discussionmentioning
confidence: 99%